Monetary policy uncertainty and firm dynamics - Stefano Fasani; Haroon Mumtaz; Lorenza Rossi (Queen Mary University of London, School of Economics and Finance, 2020)
This paper uses a FAVAR model with external instruments to show that the policy uncertainty shocks are recessionary and are associated with an increase in the exit of firms and a decrease in entry and in the stock price with total factor productivity rising in the medium run. To explain this result, we build scale DSGE module featuring firm heterogeneity and endogenous firm entry and exit. These features are crucial in matching the empirical responses. Versions of the model with constant firms or constant firms' exit are unable to re-produce the FAVAR response of firm' entry and exit and suggest a much smaller effect of this shock on real activity.
Keywords: C5; E1; E5; E6; 330; Monetary policy uncertainty shocks; FAVAR; DSGE